OPTIMIZATION OF FORMULATION OF INSULIN MICROSPHERES FOR ORAL DELIVERY - Patel, Sanjay R.; Patel, Vipul P. (Asian Journal of Pharmaceutical Research and Development, 2013)
The speculation of this research was to observe whether Eudrajit L or Eudrajit RL microspheres have the potential to serve as an oral carrier for peptide drugs like insulin. Eudragit RL-100 based Insulin loaded Microspheres were prepared by quasi-emulsion solvent diffusion method with polysorbate 20 as dispersing agent in the internal aqueous phase (IAP) and PVA/PVP as stabilizer in the external aqueous phase. The morphology of the Microspheres was studied by scanning electron microscopy (SEM).The mean particle size of formulations SP1-SP4 and PS1-PS4 in the ratios of 3:1, 6:1, 9:1 and 12:1 were found to be between 60-44µm and 62-41 µm respectively. An increase in amount of polyvinyl alcohol (emulsifying agent) from 0.5 % to 1.0 % w/v resulted in decreased production yield and increased mean particle size. An increased amount of emulsifying agent increased the mean particle size from 60 µm to 71 µm and 53 µm to 64 µm for the formulations SP1, PS1 respectively. The production yield was found to be between 70-79% for SP1-SP4, and 68-77% for PS1-PS4. The actual drug content was found to be between 62-81% for SP1-SP4, and 67-83% for PS1-PS4.